2005
DOI: 10.1152/ajpregu.00366.2004
|View full text |Cite
|
Sign up to set email alerts
|

Increased blood pressure in the offspring of diabetic mothers

Abstract: Studies were conducted in rats to determine the effect of maternal diabetes and the consequent hyperglycemia on cardiovascular function in the offspring. Diabetes was induced in pregnant Wistar rats through streptozotocin injection (50 mg/kg). Cardiovascular parameters were measured in 2-mo-old offspring animals of diabetic (OD, n ϭ 12) and control rats (OC, n ϭ 8). Arterial pressure (AP), heart rate (HR), baroreflex sensitivity, and vascular responsiveness to phenylephrine (PH) and sodium nitroprusside (SN) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0
7

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 49 publications
3
41
0
7
Order By: Relevance
“…This is in agreement with the results shown by Wichi et al [9], Magaton et al [10], and Rocha et al [12]. Salt overload beginning after weaning, as expected, also resulted in hypertension.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in agreement with the results shown by Wichi et al [9], Magaton et al [10], and Rocha et al [12]. Salt overload beginning after weaning, as expected, also resulted in hypertension.…”
Section: Discussionsupporting
confidence: 93%
“…Experimental and clinical studies have demonstrated that sustained exposure of the fetus to elevated concentrations of glucose increases the risk of intrauterine death, prematurity, perinatal mortality, and congenital malformations [4][5][6]. Increased risk for cardiovascular diseases and diabetes has been observed in the offspring of diabetic mothers at adulthood [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The MAP-HR relationship was reset toward higher pressure (rightward shift). Resetting of the baroreflex has been reported in other models of developmental programming; prenatal exposure to dexamethasone in sheep 30 or nutrition restriction in rat 31 has been shown to lead to a blunted baroreflex control of HR in adulthood, and Wichi et al 32 have demonstrated impaired baroreflex tachycardia elicited by decreasing MAP in offspring of streptozotocin-induced diabetic rats. However, the resetting of the baroreflex is commonly a consequence of hypertension 33 but has also been implicated in the development of hypertension.…”
Section: Discussionmentioning
confidence: 95%
“…In the autonomic nervous system, maternal diabetes impairs sympathetic and parasympathetic development in offspring (Fiorentini et al 2005;Young and Morrison 1998). Recently Wichi et al (2005) found that maternal diabetes impairs baroreflex control of heart rate (HR) in offspring of STZ-induced diabetic mothers. Because attenuation of baroreflex sensitivity is associated with many cardiovascular diseases including sudden death (La Rovere et al 2008), it is critically important to study the effects of maternal diabetes on the neural components within the baroreflex circuitry.…”
Section: Introductionmentioning
confidence: 99%